Hybrid approach for left-sided colonic carcinoma obstruction; a case report - Trakarnsanga, Atthaphorn (BioMed Central, 2011)
Traditionally, there are several approaches to manage left-sided colonic carcinoma obstruction, such as tumor resection with primary anastomosis, tumor resection with end-colostomy and loop-colostomy. Recently, colonic stent insertion was introduced as a bridge prior to definite surgery. We demonstrated a hybrid approach for obstructed sigmoid carcinoma using colonic stent, followed by single incision laparoscopic colectomy (SILC). A 58 year-old man presented with complete left-sided colonic obstruction. He underwent emergency colonoscopy with metallic stent placement. One week later, he was performed SILC. He recovered well after the operation without any postoperative complications. The pathological result showed adequacy of oncologic resection. This hybrid approach of colonic stent insertion and SILC can be safely performed.